Partisanship and tax competition in the American states. (20th May 2015) - Davis, John C.; Nicholson-Crotty, Sean
Abstract: Existing research identifies partisan differences in taxing choices made by state governments. Research has also found that, even when controlling for intrastate characteristics such as party, jurisdictions respond to the taxing decisions of their neighbours, particularly when citizens can easily cross-border shop. These studies treat political and competitive factors as independent influences on taxes. We suggest they are more likely to interact in taxing decisions. We argue that the political costs of cross-border shopping are higher for Republicans, and the threat of it should have a greater negative impact on taxes when that party controls major state policy-making institutions. Our analyses of state cigarette taxes between 1980 and 2011 confirm that a higher threat of cross-border shopping has a larger negative impact on taxes under Republican governors. We conclude that, by missing the interaction between partisanship and the threat of fiscal mobility, previous work misestimates key influences on tax competition.